2017
DOI: 10.1177/1178623x17703382
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Lesion: Image, Clinical Presentation, and Treatment

Abstract: In this article, the cause, histology, imaging characteristics, clinical presentation, and treatment of these lesions are thoroughly discussed. Bone marrow edema is the generic term classically used to describe the high-signal-intensity alterations detected on magnetic resonance fluid-sensitive sequences. The significance of bone marrow edema for the patient’s clinical condition and the prognosis of the affected joint is being increasingly investigated and discussed, and situations characterized by subchondral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 28 publications
0
42
0
Order By: Relevance
“…The largest of these trials, conducted by Cohen and Sharkey, 22 showed that 88% of patients (50 of 57) reported positive improvements in pain scores 6 months after receiving subchondroplasty. Similarly, Bonadio et al 6 and Farr and Cohen 19 showed improvements in pain metrics such as the visual analog scale score, as well as the Knee Injury and Osteoarthritis Outcome Score, International Knee Documentation Committee score, and 12-item Short Form Health Survey score. Yoo et al 21 reported that patients who first received SCP and then later underwent total or unicompartmental knee arthroplasty showed no difference in outcomes compared with patients who underwent arthroplasty alone, suggesting that SCP may not compromise the results of subsequent arthroplasty treatment.…”
Section: Subchondroplasty For Hip Bone Marrow Lesions E871mentioning
confidence: 79%
See 2 more Smart Citations
“…The largest of these trials, conducted by Cohen and Sharkey, 22 showed that 88% of patients (50 of 57) reported positive improvements in pain scores 6 months after receiving subchondroplasty. Similarly, Bonadio et al 6 and Farr and Cohen 19 showed improvements in pain metrics such as the visual analog scale score, as well as the Knee Injury and Osteoarthritis Outcome Score, International Knee Documentation Committee score, and 12-item Short Form Health Survey score. Yoo et al 21 reported that patients who first received SCP and then later underwent total or unicompartmental knee arthroplasty showed no difference in outcomes compared with patients who underwent arthroplasty alone, suggesting that SCP may not compromise the results of subsequent arthroplasty treatment.…”
Section: Subchondroplasty For Hip Bone Marrow Lesions E871mentioning
confidence: 79%
“…The lesions are visualized as regions of hyperintensity on fatsuppressed T2-weighted magnetic resonance imaging (MRI) sequences. 6,7 Plain radiographic imaging of patients with BMLs will often show femoroacetabular impingement (FAI), which can complicate surgical management if a delamination injury to the acetabular articular cartilage is present. [8][9][10][11][12][13] Gdalevitch et al 14 showed that radiographic visualization of delamination cystsdcaused by leakage of intra-articular joint fluid into subchondral bone due to microfractures caused by delamination of articular cartilagedin the anterosuperior part of the acetabulum could predict delamination of the acetabular articular cartilage adjacent to labral tears with 80% sensitivity and 96.3% specificity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…BML may not be apparent on radiographs and are diagnosed on magnetic resonance imaging (MRI) using fat-saturated T2-weighted, proton densityweighted or short tau inversion recovery (STIR) image sequences [5,6]. They appear as poorly defined areas of high signal intensity in the subchondral region [5][6][7][8]. These lesions represent sites of increased mechanical stress [9] with subchondral hyperintense signal suggestive of an insufficiency fracture [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow lesions (BMLs) are an important feature of knee OA and are the target of certain therapeutic interventions (15,16). Both effusion and BMLs have been independently associated with OA as well as pain in OA (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%